2022
DOI: 10.1111/psyg.12827
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the five‐item version of the Geriatric Depression Scale (GDS‐5) in a Turkish elderly population

Abstract: Background: Late-life depression is a geriatric syndrome which should be taken seriously. Many clinical scales have been developed for the screening of geriatric depression. Most of these have been validated at different times and in diverse populations. A five-question version of the Geriatric Depression Scale (GDS-5) was developed in 1997. This test has been validated and used in different populations. In the present study, we plan to validate the GDS-5 for the Turkish elderly population. Methods: Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…2 Thus, we found that the TGDS-5 and the original GDS-5 have only one common item ('Do you often get bored?'). 1,2 Other items differed from the GDS-5; however, the Cronbach's α of the TGDS-5 increased to 0.807, that is, the internal consistency coefficient was 'good'. 1,2 In our study, although the specificity and positive predictive value (PPV) of the GDS-5 were high, its sensitivity value was significantly lower, and low a sensitivity value for a screening tool limits its use.…”
Section: Dear Editormentioning
confidence: 98%
See 4 more Smart Citations
“…2 Thus, we found that the TGDS-5 and the original GDS-5 have only one common item ('Do you often get bored?'). 1,2 Other items differed from the GDS-5; however, the Cronbach's α of the TGDS-5 increased to 0.807, that is, the internal consistency coefficient was 'good'. 1,2 In our study, although the specificity and positive predictive value (PPV) of the GDS-5 were high, its sensitivity value was significantly lower, and low a sensitivity value for a screening tool limits its use.…”
Section: Dear Editormentioning
confidence: 98%
“…1,2 However, due to the fact that these studies were conducted in two different sociocultural regions of Turkey, the sensitivity of the GDS-5 was higher (96.4% vs 85.8%) and the specificity was lower (67.7% vs 92.1%) depending on the differences in the education levels of the participants. 1,2 However, the important finding common to both studies is that the Cronbach's α value is below 0.7, that is, the internal consistency coefficient is at a questionable level, which means that the GDS-5 or some of its items do not represent respondents with depression. 3,4 To solve this problem, by performing Kappa consistency analysis, the inter-rater reliability of each of the items in the long form of the GDS can be checked, and community-specific short forms can be produced with those items having the highest kappa values.…”
Section: Dear Editormentioning
confidence: 99%
See 3 more Smart Citations